Traffic System on the Island of Krk - Dadić, Ivan; Petrinović, Tomislav; Brlek, Predrag (Promet - Traffic&Transportation, 2012)
The construction of the bridge mainland - Krk has integratedthe island of Krk into a unique road traffic system ofRijeka and the Croatian seaside. The bridge, together with theferryboat lines Senj and Baska, have significantly improved thetraffic connections of the islands of Cres and Rab, especiallywith Rijeka and the seaside of the counties: Primorsko-goranskaand Licko-senjska and Istarska zupanija.Apart from the connection of the island of Krk with themainland and the neighbouring islands, also the interurbanconnections within the islands are very important.The development of tourism will increase the significanceof the Krk Airport, especially during the tourist season.